Drivers of maternity care in high-income countries: can health systems support woman-centred care?. Issue 10057 (5th November 2016) - Shaw, Dorothy; Guise, Jeanne-Marie; Shah, Neel; Gemzell-Danielsson, Kristina; Joseph, KS; Levy, Barbara; Wong, Fontayne; Woodd, Susannah; Main, Elliott K
Summary: In high-income countries, medical interventions to address the known risks associated with pregnancy and birth have been largely successful and have resulted in very low levels of maternal and neonatal mortality. In this Series paper, we present the main care delivery models, with case studies of the USA and Sweden, and examine the main drivers of these models. Although nearly all births are attended by a skilled birth attendant and are in an institution, practice, cadre, facility size, and place of birth vary widely; for example, births occur in homes, birth centres, midwifery-led birthing units in hospitals, and in high intervention hospital birthing facilities. Not all care is evidenced-based, and some care provision may be harmful. Fear prevails among subsets of women and providers. In some settings, medical liability costs are enormous, human resource shortages are common, and costs of providing care can be very high. New challenges linked to alteration of epidemiology, such as obesity and older age during pregnancy, are also present. Data are often not readily available to inform policy and practice in a timely way and surveillance requires greater attention and investment. Outcomes are not equitable, and disadvantaged segments of the population face access issues and substantially elevated risks. At the same time, examples of excellence and progress exist, from clinical interventions to models of care and practice. Labourists (who provide care for all the facility's women for labour and delivery) are discussed as a potential solution. Quality and safety factors are informed by women's experiences, as well as medical evidence. Progress requires the ability to normalise birth for most women, with integrated services available if complications develop. We also discuss mechanisms to improve quality of care and highlight areas where research can address knowledge gaps with potential for impact. Evaluation of models that provide woman-centred care and the best outcomes without high costs is required to provide an impetus for change.